2019
DOI: 10.1002/fam.2742
|View full text |Cite
|
Sign up to set email alerts
|

Influence of liquid accelerant on scaling behavior of stainless steel in fire: An experimental study

Abstract: Summary Among the commercial materials, stainless steel is widely used in our daily life and can be hardly destroyed by flame or the heat emanating from a fire. In this fundamental work, the formation and development of oxide scale on stainless steel 1Cr11Ni2W2MoV were investigated at 600°C to 800°C in the atmospheres with and without liquid accelerant. The aim of this work is to figure out the influence of accelerant on the oxidation pattern of stainless steel at high temperature that occurs in a fire. The mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…The results showed that the high-temperature oxidation rate of Q235 was significantly accelerated by kerosene combustion smoke. [7][8][9] Existing studies on steel oxide layers in fire atmosphere have primarily focused on smoke with temperatures above 600 C from accelerants. At an actual fire scene, however, a large number of combustibles made of hydrocarbons are present, but the corresponding impact of the burning atmosphere on the steel pattern evolution under high temperatures remains unclear.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results showed that the high-temperature oxidation rate of Q235 was significantly accelerated by kerosene combustion smoke. [7][8][9] Existing studies on steel oxide layers in fire atmosphere have primarily focused on smoke with temperatures above 600 C from accelerants. At an actual fire scene, however, a large number of combustibles made of hydrocarbons are present, but the corresponding impact of the burning atmosphere on the steel pattern evolution under high temperatures remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…To analyze the impact of the atmosphere formed by accelerants on the steel oxide layer, Xie et al investigated the oxidation behavior of Q235 carbon steel in air and kerosene combustion smoke under high temperatures. The results showed that the high‐temperature oxidation rate of Q235 was significantly accelerated by kerosene combustion smoke 7–9 …”
Section: Introductionmentioning
confidence: 99%
“…Herein, the oxidation behavior of metallic materials present in the combustion atmosphere was used to judge the presence of the accelerants in a fire scene based on this theory. Previous studies demonstrated that the oxidation characteristics of carbon, steel, copper, aluminum alloys, and stainless steel materials may be closely related to the oxide properties alerted by the combustion byproducts in combustion environments 13 17 . Carbon produced during the combustion of accelerants can have a range of effects on formation of the oxide layer on metal surfaces and facilitates the inference of the type of accelerant present in the combustion environment.…”
Section: Introductionmentioning
confidence: 99%